GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1785 species occurrences available in GBIF matching the query: TaxonKey: Cedrela odorata L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 1785 records from 129 constituent datasets: 1 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Phanerogamic Botanical Collections (S). 1 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from UFG - Herbário da Universidade Federal de Goiás. 2 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 14 records from IAC - Herbário do Instituto Agronômico de Campinas. 2 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 1 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 25 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from SPSF - Herbário Dom Bento José Pickel. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 4 records from PRECIS. 10 records from SPF - Herbário da Universidade de São Paulo. 2 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 4 records from UFP - Herbário UFP - Geraldo Mariz. 21 records from Colección Herbario Federico Medem Bogotá - FMB. 3 records from HERBAM - Herbário da Amazônia Meridional. 1 records from Herbario Pontificia Universidad Javeriana. 3 records from IICT Herbário LISC. 40 records from Herbario Universidad de Antioquia (HUA). 7 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 2 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 8 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from Colección Herbario Universidad Católica de Oriente. 1 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 30 records from Plantae of Costa Rica (INBio). 14 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from Herbarium areqvipense (HUSA). 3 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 9 records from Australia's Virtual Herbarium. 1 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 3 records from Plantas Bosque Seco Chicamocha. 4 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 18 records from iNaturalist Research-grade Observations. 3 records from CONN. 2 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 6 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 8 records from ALCB - Herbário Alexandre Leal Costa. 3 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 7 records from ASE - Herbário da Universidade Federal de Sergipe. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 3 records from FUEL - Herbário da Universidade Estadual de Londrina. 12 records from ICN - Universidad Nacional de Colombia. 143 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 64 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 4 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 491 records from Tropicos Specimen Data. 30 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 2 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 7 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 1 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5 records from Lista florística preliminar de Tamaulipas. 1 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 3 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 2 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 4 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 1 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Bosques. 9 records from Inventario nacional de especies vegetales y animales de uso artesanal. 3 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Nectar. 16 records from Formación del banco de datos del herbario (UCAM). 2 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 1 records from Base de datos sobre la flora de Durango. 5 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 4 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 1 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 2 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 6 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 13 records from NMNH Extant Specimen and Observation Records. 2 records from Andes to Amazon Biodiversity Program. 1 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 7 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Jardín Botánico de Córdoba: Herbarium COA. 1 records from Auckland Museum Botany Collection. 19 records from herbario. 2 records from Plants of Papua New Guinea. 1 records from Biologiezentrum Linz. 48 records from Árboles y Arbustos Nativos para la Restauración Ecológica y Reforestación de México (IE-DF,UNAM). 34 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 1 records from USF Herbarium. 165 records from Field Museum of Natural History (Botany) Seed Plant Collection. 10 records from MBML-Herbario - Herbário Mello Leitão. 2 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 4 records from University of Ghana - Ghana Herbarium. 12 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 1 records from Jardín Botánico Uniamazonia JBUA. 2 records from UPCB - Herbário do Departamento de Botânica. 3 records from Lund Botanical Museum (LD). 9 records from Geographically tagged INSDC sequences. 1 records from TEPB - Herbário Graziela Barroso. 5 records from HVASF - Herbário Vale do São Francisco. 4 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 1 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 3 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Bernice P. Bishop Museum. 7 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 25 records from Instituto de Ciencias Naturales. 5 records from Census of species recorded during phytosociological surveys in Benin. 3 records from JPB - Herbário Lauro Pires Xavier. 7 records from EAC - Herbário Prisco Bezerra. 67 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 3 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 95 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 5 records from UB - Herbário da Universidade de Brasília. 1 records from Herbarium - Las Cruces Biological Station. 5 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 7 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 14 records from African Plants - a photo guide. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 1 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 4 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from SysTax - Herbaria. 4 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 24 records from Geneva Herbarium – General Collection (G). 14 records from Instituto de Botánica Darwinion. 1 records from JOIw - Xiloteca Joinvillea. 1 records from CAS Botany (BOT). 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 2 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from HRCB - Herbário Rioclarense. 1 records from PACA-AGP - Herbarium Anchieta. 1 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences